Sustainable development of the world energy taking into account dynamic of energy intensity: current trends and long-term forecast. (October 2018) - Eder, L.V.; Provornaya, I.V.; Filimonova, I.V.
Abstract: Based on the comparative analysis of the existing econometric characteristics, it has been shown that the exponential trend is the best trend describing the energy intensity of an economy in permanent and variable prices. The presence of the exponential trend in the energy intensity reduction indicates that the rates of enhancing the efficiency of energy consumption reduce uniformly in time. It is proposed in this work to consider beta convergence for countries not at equal intervals of time but from the moment of the start of reduction for each specific region. In this work, a close relationship is demonstrated for countries between the rate of energy intensity reduction and the initial value of the energy intensity considered. Based on the revealed regularities, forecast of the change in the energy intensity of the economy was made for a long-term perspective till 2040.